The Association Between Physical Activity and Monocyte-HDL Ratio in Diabetes Mellitus Patients Who Have Exceed Life Expectancy in Yogyakarta Province - Setiawan, Gibran Ilham; Probosuseno, Probosuseno; Sinorita, Hemi (Acta Interna The Journal of Internal Medicine, 2024)
Background: The elderly population is expected to double in the upcoming three decades, due to increase in life expectancy. The province of DIY has the highest life expectancy in Indonesia (73.13 years and 76.67 years for men and women). Physical activity can reduce insulin resistance, improve lipid metabolism and reduce levels of inflammation in diabetes mellitus (DM). Physical activity can increase life expectancy. Many factors affect life expectancy, one of which is physical activity. This study investigated the association between physical activity and monocyte to HDL ratio (MHR) in diabetes mellitus patients who had exceeded their life expectancy in Yogyakarta.Method: This cross-sectional study was conducted in September 2022-April 2023 and using purposive sampling. Participants who meet the criteria and consent were asked to fast at least 8 hours, then be interviewed by a physical activity questionnaire and checked complete blood tests, fasting blood glucose and HDL cholesterol. The association between physical activity and MHR then analyzed using SPSS.Result: There were 50 participants with median age 78 (74-91) years. The mean score of physical activity is 100.28±7.96. Mean MHR is 0.0147±0.005. There is a significant relationship with weak correlation between physical activity and MHR (p 0.034, r -0.301), weak correlation between MHR and body mass index (BMI) (p 0.015, r 0.343), obesity (p 0.019, r 0.331) central obesity (p 0.032, r 0.303) and smoking (p 0.039, r 0.293). Multivariate analysis was performed, there is a significant relationship with weak correlation between physical activity and MHR (p 0.033, r -0.297).Conclusion: There is a negative correlation with weak strength between physical activity and MHR in patients with diabetes mellitus who have reached the life expectancy of province of DIY.